Is Nuclear Power Generation a Viable Alternative to the Energy Needs of Pakistan? SWOT-RII Analysis - Abbasi, Sikander Ali; Harijan, Khanji; Mengal, Abdullah; Shaikh, Faheemullah; Mirjat, Nayyar Hussain (International Journal of Energy Economics and Policy, 2021)
Pakistan has faced a severe energy crisis for the last two decades. With the considerable power generation expansion, the country still faces power outages with an unsustainable energy mix. Successive energy policies emphasized thermal power deployment which has proved to be a part of the problem. Therefore, the present study has attempted to evaluate and investigate the prospects of nuclear power as a viable alternative in terms of energy security, reliability, and environmental sustainability with the SWOT tool. To further quantify the main drivers and barriers of nuclear energy, a Relative Importance Index (RII) analysis has been done. The results reveal that Pakistan has decades of experience running nuclear power plants satisfactorily. The regulatory framework for nuclear power generation is adequate to expand nuclear power generation. The opportunities are enormous to meet Sustainable Development Goal (SDG), as nuclear is a carbon-free source of energy. The main barriers are global suspicion of nuclear proliferation and less social acceptance. Keywords: SWOT, Delphi, RII Analysis, Nuclear Power Generation JEL Classifications: P4, Q4 DOI: https://doi.org/10.32479/ijeep.11122